Association between anemia and frailty in 13,175 community-dwelling adults aged 50 years and older in China - Ye Ruan (2020)
© 2019 The Author(s). Background: Anemia and frailty contribute to poor health outcomes in older adults; however, most current research in lower income countries has concentrated on anemia or frailty alone rather than in combination. The aim of the present study was to investigate the association between anemia and frailty in community-dwelling adults aged 50 years and older in China. Methods: The study population was sourced from the 2007/10 SAGE China Wave 1. Anemia was defined as hemoglobin less than 13 g/dL for men and less than 12 g/dL for women. A Frailty Index (FI) was compiled to assess frailty. The association between anemia and frailty was evaluated using a 2-level hierarchical logistic model. Results: The prevalence of anemia was 31.0% (95%CI: 28.4, 33.8%) and frailty 14.7% (95%CI: 13.5, 16.0%). In the univariate regression model, presence of anemia was significantly associated with frailty (OR = 1.62, 95% CI: 1.39, 1.90) and the effect remained consistent after adjusting for various potential confounding factors including age, gender, residence, education, household wealth, fruit and vegetable intake, tobacco use, alcohol comsumption and physical activity (adjusted OR = 1.31, 95% CI:1.09, 1.57). Each 1 g/dL increase in hemoglobin concentration was associated with 4% decrease in the odds of frailty after adjusting for several confounding variables (adjusted OR = 0.96, 95% CI: 0.93, 0.99). Conclusion: Anemia and low hemoglobin concentrations were significantly associated with frailty. Therefore, health care professionals caring for older adults should increase screening, assessment of causes and treatment of anemia as one method of avoiding, delaying or even reversing frailty.